THE MAIN DIRECTIONS OF THE BUILDING PRODUCTION INNOVATIVE DEVELOPMENT - T. A. Faruhov; A. M. Esetova (Вестник Дагестанского государственного технического университета: Технические науки)
Objective foundations and perspective directions of the construction industry innovative development have been analytically generalized. The mechanism of the innovative activity stimulation system improvement of construction companies has been proposed.